2016
DOI: 10.1172/jci82529
|View full text |Cite
|
Sign up to set email alerts
|

Schlafen 4–expressing myeloid-derived suppressor cells are induced during murine gastric metaplasia

Abstract: Chronic Helicobacter pylori infection triggers neoplastic transformation of the gastric mucosa in a small subset of patients, but the risk factors that induce progression to gastric metaplasia have not been identified. Prior to cancer development, the oxyntic gastric glands atrophy and are replaced by metaplastic cells in response to chronic gastritis. Previously, we identified schlafen 4 (Slfn4) as a GLI1 target gene and myeloid differentiation factor that correlates with spasmolytic polypeptide-expressing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(99 citation statements)
references
References 54 publications
5
94
0
Order By: Relevance
“…A study by the Merchant laboratory identified Schlafen 4 ( Slfn4 ) as a GLI1 target gene and myeloid differentiation factor that correlated with the development of SPEM in mice 77 . A recent study by the same group then showed that migration of Slfn4-expressing cells from the bone marrow to the stomach in response to Helicobacter infection showed MDSC markers, and acquired the ability to inhibit T-cell proliferation 78 . This supports MDSC suppression of T-cell function and subsequent dampening of the immune response to create a microenvironment favoring tumor growth 79 …”
Section: Maintenance Of Gastric Cancer: the Role Of The Cancer Stem Cmentioning
confidence: 99%
“…A study by the Merchant laboratory identified Schlafen 4 ( Slfn4 ) as a GLI1 target gene and myeloid differentiation factor that correlated with the development of SPEM in mice 77 . A recent study by the same group then showed that migration of Slfn4-expressing cells from the bone marrow to the stomach in response to Helicobacter infection showed MDSC markers, and acquired the ability to inhibit T-cell proliferation 78 . This supports MDSC suppression of T-cell function and subsequent dampening of the immune response to create a microenvironment favoring tumor growth 79 …”
Section: Maintenance Of Gastric Cancer: the Role Of The Cancer Stem Cmentioning
confidence: 99%
“…All mouse experiments were approved by the University of Michigan’s Institutional Animal Care and Use Committee. Transgenic Shh mice (promoter for cytomegalovirus [pCVM]‐ Shh ) and Gli1 lacZ/lacZ mice have been described . The Gli1 lacZ./+ and Gli1 lacZ./lacZ mice contain a knock‐in lacZ , encoding a nuclear‐localized β‐galactosidase, into exon 2 of the mouse Gli1 gene, producing a null allele .…”
Section: Methodsmentioning
confidence: 99%
“…HH signaling involves Sonic hedgehog (SHH) and Indian hedgehog (IHH) ligands, the receptor Patched‐1 (PTCH1), and their transcriptional effectors glioma‐associated oncogene 1 (GLI1), GLI2, and GLI3 . In the canonical HH pathway, cells expressing HH ligand signal to stromal cells expressing PTCH1 and GLIs in a variety of gastrointestinal tissues . In the liver, HH ligands are expressed in both epithelial cells and myofibroblasts after injury, and HH signaling is responsible for the “reactive” phenotype of injured cholangiocytes .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloid cell polarization into MDSCs requires hedgehog-regulated transcription factor GLI1, which induces gastric MDSCs to express Schlafen 4 , a myeloid differentiation factor. 79 Dr Merchant showed that a nucleic acid signature for MDSCs in plasma correlates with gastric metaplasia presence in both mice and humans. Collectively, her studies suggest that MDSCs are present in the gastric microenvironment before neoplastic transformation, and that they might serve as a biomarker for gastric cancer risk.…”
Section: Inflammation and The Development Of Metaplasia Sessionmentioning
confidence: 99%